A method of Evaluating Development Priority Based on Inventory of Water Resources in Arid and Semi-arid Area - Vangani, N S; Chatterji, P C (Annals of Arid Zone, 2016)
Availability of water is one of the important factors for the development of any area, specially for arid and semi-arid areas. So far very little importance is being paid to evaluate various parameters governing the water potential of any area while formulating any development plan. In this paper authors have suggested the method for evaluating various parameters governing the surface and ground water potentials which would give a sound basis for formulating a development plan and assessing the priority areas.